"If you don't have enough equipment, you're not going to provide quality services": Healthcare workers' perceptions on improving the quality of antenatal care in rural Tanzania. (2020) - van Pelt, Sandra; Massar, Karlijn; van der Eem, Lisette; Shields-Zeeman, Laura; de Wit, John B.F.; Ruiter, Robert A.C.
Highlights: Healthcare workers perceive variation in the quality of antenatal care provision. Healthcare workers experience several barriers that negatively influence their work motivation. An electronic decision support system could improve the work motivation of healthcare workers. Abstract: Introduction: To reduce maternal mortality in rural Tanzania, improving antenatal care remains an urgent priority. Therefore, the availability of qualified and motivated staff providing antenatal care is an essential precondition for high-quality maternal healthcare. However, it is still unclear which factors affect the performance of healthcare workers in this setting, and what they perceive is necessary to improve the quality of antenatal care. The aim of this research was to identify factors that could, according to healthcare workers, improve their performance and thereby improve the quality of antenatal care in rural Tanzania. Methods: Semi-structured in-depth interviews were conducted with sixteen healthcare workers of different education levels and from different health facilities in Magu District, Tanzania. Questions were asked about their experiences, opinions, and motivations related to the provision and quality of antenatal care, as well as their perceptions of the value of using an e-health application during consultations. Results: Healthcare workers possess a positive attitude towards antenatal care and acknowledge its importance. Despite the existing social pressure from both colleagues and clients to perform well, this study identified differences in the quality of antenatal care provision and the level of motivation between healthcare workers. In addition, participants felt capable of providing antenatal care but complained about the poor working conditions (e.g. lack of electricity, equipment or medication), and indicated a need for more training and better supervision. Furthermore, when asked whether an electronic clinical decision and support system could improve the quality of antenatal care and their working conditions, healthcare workers expressed a positive attitude towards such a system. Discussion: In order to change the status quo in antenatal care provision in Tanzania, attention should be paid to reducing the work challenges experienced by healthcare workers. This could be achieved through providing training opportunities, supportive leadership, and the improvement of physical working conditions, for example by the implementation of an electronic clinical decision and support system.